(untitled) (Research, Society and Development, 2020)
This research emerged through studies in the writing course for the elaboration of Thesis, related to the Doctorate in Science Education and Mathematics (REAMEC), with reference in the pole of the State University of Amazonas (UEA), with the intention of involving Iinclusive Education, Visual Impairment and Chemistry Teaching. Through a mapping of research published in the 1997-2017 ENPECs, the research has bibliographic character and presents as reference, the proposal of questions conducted by the author, referenced by a continuous reconstruction, understanding to be the chemistry teacher, a subject capable of learning, invent and create ’em’ and ’during’ your way in the classroom. we dare to arouse the awakening of a criticism, reflection and change of attitude, in the sense of a personal look of the teaching Professional himself, to his own Professional practice, for this we categorize the work in two parts: Curriculum Content (CC) and Inclusive Teaching Resources (RDI). it is noticed in the works published in the ENPECs, a qualitative approach, which have as reference (CC) the periodic table, where 57% of the workers bring it as (RDI) built in the classroom. However, huge gaps exist in the making of (RDI) that make learning of (CC) available at all levels of education.